The Effect of the Bitcoin Economy on Money Supply with the Bitcoin Value Volatility as Intervening Variable - Valya Raissa Kirana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2020)
In this technological era, Cryptocurrency emerged as a means of payment. One example is Bitcoin which has been widely used as a virtual currency. The Bitcoin system itself is based on Cryptocurrency and is decentralized and uses peer-to-peer networking and cryptography-based technology that can maintain the integrity of the data. With the easy use of Bitcoin, the demand for Bitcoin continues to increase every year while the limited amount of Bitcoin causes the value of Bitcoin to experience volatility. This study was conducted to determine whether there is an influence between the economic variables of bitcoin, currency bitcoin as an intervening variable, and the money supply in the country of Thailand. This research uses observation years January 2016 - June 2019. The methods used are Descriptive Statistics, Simple Linear Regression, test Classical Assumptions, and t test. The results show that the bitcoin economy has a significant positive effect on the bitcoin currency but the bitcoin currency does not affect the amount of money supply and the currency bitcoin is not an intervening variable because the bitcoin economy can directly influence the amount of money supply without passing through the currency bitcoin first, meaning that the people in Thailand still use bitcoin as an investment tool not as a transaction tool.